Analysis Of The Number Of General Doctors Needs With The Health Workload Analysis Method At The Public Poli Uptd Puskesmas Jatirahayu, Bekasi City, 2021 - Ruth Vivian; Acim Heri Iswanto; Cahya Arbitera (Universitas Widya Gama Mahakam Samarinda, 2022)
Background: Human resource planning is a series of processes that are useful for investing resources with various information and strategies in order to to achieve agency goals. One of the health human resource planning methods is to use the health workload analysis method issued by BPPSDMK RI in 2015. Objectives: This study aims to analyze the optimal number of general doctors in General Poly at Jatirahayu Primary Health Care of Bekasi City in 2021. Research Methods: This study uses the health workload analysis method. The research design is descriptive qualitative with research instruments, namely, work sampling and interviews. Results: The result of this study indicate that the working time of general doctors is 78.180 minutes/year. Then, the workload standard of the general doctors was 17.373,34 for medical services, 9.984,67 for follow-up services, and 7.474,19 for referral-making services. The supporting task standard was 1,96. The results of the calculation using the health workload analysis method found that there was a shortage of 3 general doctors. Conclusion: Based on the results of the study, it is hoped that it can become a consideration for primary health care regarding the addition of general doctors and evaluations so that the quality of service can be improved.